2007
DOI: 10.1159/000099350
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Natural Progression of Medullary Sponge Kidney and a Novel Grading System Based on Intravenous Urography Findings

Abstract: Purpose: Medullary sponge kidney (MSK) is a developmental abnormality of the medullary pyramids of the kidney, characterised by cystic dilatations of the collecting ducts. We investigated a cohort of patients with MSK to gain further information about its presentation, clinical course and treatment required. We devised a grading system based upon findings at diagnostic intravenous urography (IVU) and established a relationship between severity of IVU findings and severity of disease. Materials and Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
13
0
3
Order By: Relevance
“…Moreover, it has been shown that radiographic findings also have prognostic importance. In a retrospective study, Forster et al [24 ]showed a strong correlation of the severity of radiologic and clinical features in MSK.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that radiographic findings also have prognostic importance. In a retrospective study, Forster et al [24 ]showed a strong correlation of the severity of radiologic and clinical features in MSK.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Morbidity is estimated at one in 5,000 to 20,000 people. 8 Although most patients with MSK remain asymptomatic, 2.6 to 20z demonstrate clinical symptoms, such as renal colic, urinary tract infection, and macrohematuria due to urinary stones. 2,9 Therefore, MSK is mainly diagnosed by kidney-ureter-bladder radiography (KUB) and IVU.…”
Section: Discussionmentioning
confidence: 99%
“…8 FMD tends to affect young to middle age white women and may involve almost any artery as well as multiple arterial beds. 9,10 Often, bilateral renal, splanchnic, extremities, and asymptomatic cerebrovascular involvement is found during angiographic investigation.…”
Section: Discussionmentioning
confidence: 99%